PEER EVALUATION TO TEACH SEMANTICS - Syaputri, Wuri (Jurnal Smart, 2016)
This study begins from the problem of student’s confidence to express their knowledge in order to support their understanding the references in learning semantics. The objective of this study knows the significance of achievement process in Semantics class. The technique of this study is using peer evaluation to conduct semantics class. Method of the study is using classroom action research with questionnaire, test and documentation during the semester. The result showed the raising reaction of the students’ confidence in expressing their knowledge. It was proven by the gain of the students score in cycle 1 and 2. Keywords: Semantics, Peer Evaluation, Achievement